2014
DOI: 10.1002/ijc.28883
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PrPc, combined with MGr1‐Ag/37LRP, is predictive of poor prognosis in gastric cancer

Abstract: Prion protein (PrPc) has been previously reported to be involved in gastric cancer (GC) development and progression. However, the association between expression of PrPc and GC prognosis is yet poorly characterized. In the present study, the expressions of PrPc and MGr1-Ag/37LRP, a protein interacting with PrPc, were detected using the tissue microarray technique and immunohistochemical method to compare clinicopathological parameters of 238 GC patients. We found that the expressions of PrPc and MGr1-Ag/37LRP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 38 publications
1
43
0
1
Order By: Relevance
“…miRNAs, including miR-27a, miR-497, miR-363, miR-181b, miR-15b and miR-16, have been reported to be implicated in the MDR of GC (Ishimoto et al, 2016;Riquelme et al, 2016;Song and Ajani, 2013;Xia et al, 2008;Zhang et al, 2016;Zhu et al, 2010). Our previous studies identified 11 miRNAs, which regulate MDR in GC, using high-throughput functional screening, and further confirmed that miR-27b/CCNG1/P53/miR-508-5p axis plays important roles in GC-associated MDR (Shang et al, 2016;Shang et al, 2014). Here we identified miR-20a as an upstream miRNA of LRIG1, playing an important role in GC 1 1 drug resistance.…”
Section: Discussionsupporting
confidence: 67%
“…miRNAs, including miR-27a, miR-497, miR-363, miR-181b, miR-15b and miR-16, have been reported to be implicated in the MDR of GC (Ishimoto et al, 2016;Riquelme et al, 2016;Song and Ajani, 2013;Xia et al, 2008;Zhang et al, 2016;Zhu et al, 2010). Our previous studies identified 11 miRNAs, which regulate MDR in GC, using high-throughput functional screening, and further confirmed that miR-27b/CCNG1/P53/miR-508-5p axis plays important roles in GC-associated MDR (Shang et al, 2016;Shang et al, 2014). Here we identified miR-20a as an upstream miRNA of LRIG1, playing an important role in GC 1 1 drug resistance.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, more recently it was suggested that PrP C might also promote human tumor development and diffusion, and the induction of drug resistance [22, 36]. PrP C overexpression was observed in gastric cancer lesions as compared to non-tumor tissues representing a predictive marker of poor prognosis [66], while PrP C down-regulation reduced tumor cell proliferation [67] or caused cell death via the activation of the autophagic pathway [68]. However, most of these studies have been performed in continuous cell lines evaluating the effects of PrP C on the biological behavior of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Chieng and Say (2015) found that overexpression of PrP C in a colon adenocarcinoma cell line increased invasiveness, whilst a study of pancreatic ductal adenocarcinoma patients reported that PrP C -positive tumours were associated with reduced survival time from diagnosis (Sy et al, 2011). PrP C expression was also shown to be upregulated in cancerous tissue from human gastric cancer patients compared with adjacent non-cancerous tissue from the same individuals (Zhou et al, 2014), although a recent study of a larger patient group found the opposite correlation (Tang et al, 2016). …”
Section: Prpc Functionmentioning
confidence: 99%